How realistic is a racehorse simulator?. Issue 14 (3rd October 2016) - Walker, A.M.; Martin, A.; Pfau, T.; Sparkes, E.L.; Wilson, A.M.; Witte, T.H.
Abstract: Race jockey training is demanding and technical. Increased horse care costs and demands on time have led to greater availability and use of racehorse simulators during training. Little is known about the accuracy of the simulated movement and therefore how effective they are for developing the desired technique. We quantified and compared sacral rotation and displacement vectors for a racehorse simulator and a real galloping horse. A single inertial measurement unit was placed on the sacrum of six horses (horse) during a training gallop along an all-weather seven furlong gallop and on the highest speed setting 'four' on the simulator. Displacements were calculated in all three axes before being cut into cycles and analysed along with roll and pitch. Displacement and rotation amplitudes were extracted and compared for the horse and simulator. Horse sacral movement parameters were more varied than those recorded on the simulator. The real horse exhibited greater dorso-ventral, medio-lateral and roll amplitude but smaller cranio-caudal displacement amplitude and no difference in pitch amplitude. Displacement trajectory of the simulator when viewed laterally from the left side, was anticlockwise, the opposite direction to that of the real horse leaving the regular use of a simulator during jockey training under question. Use of the racehorse simulator is beneficial to develop specific fitness and to enable physical manipulation into the optimal position. Care must be taken to avoid any detrimental effects of training with the opposite movement trajectory to that experienced during a race. The programming of the simulators may benefit from adaptations to maximise their benefits.